Detection and Molecular Characterization of Methicillin-Resistant Staphylococcus aureus Isolated from Bulk Tank Milk of Cows, Sheep, and Goats - Tegegne, Henok Ayalew; Florianová, Martina; Gelbíčová, Tereza; Karpíšková, Renáta; Koláčková, Ivana (Foodborne pathogens and disease, 2019)
This study is aimed at detecting and characterizing methicillin-resistant Staphylococcus aureus (MRSA) from bulk tank milk samples of cows, sheep, and goats collected from dairy farms in the Czech Republic. All MRSA isolates were identified using PCR detection of the Staphylococcus aureus-specific fragment SA442 and mecA gene. The staphylococcal chromosomal cassettes mec (SCCmec), spa, and multilocus sequence types (MLST) were determined. The presence of genes encoding enterotoxins (ses), Panton-Valentine leukocidin (pvl), exfoliative toxins A, B (eta, etb), and toxic shock syndrome toxin (tst) were assessed. To differentiate human and animal origin, the presence of staphylokinase (sak) gene, ϕSa3 prophage, and susceptibility to tetracycline was tested. Out of 49 bulk tank milk samples examined, 14 (28.6%) were MRSA-positive. Eleven positive samples came from cow's milk (38%) and the remaining three from goat's milk (33%). All samples of ewe's milk were negative. In MRSA isolates three sequence types containing seven spa types were identified. Twelve isolates (85.7%) belonged to ST398 spa types t011/SCCmec IVa, t011/SCCmec V, t034/SCCmec V, t1456/SCCmec IVa, t1255/SCCmec V, and t2346/SCCmec V. Another two isolates belonged to ST5/t3598/SCCmec IVa and ST8/t064/SCCmec IVNT. In six isolates, one or more ses genes (seb, sed, seg, sei, and sej) were confirmed. One isolate from cow's milk harbored the tst gene. Another two isolates (ST398/t1456/SCCmec IVa and ST5/t3598/SCCmec IVa) harbored the sak gene and ϕSa3 prophage, and the latter was the only tetracycline-susceptible isolate in this study. However, none of the isolates was positive for pvl or eta, etb. These results suggest that there is the wide geographical spread of ST398 across different regions of the Czech Republic with no host preference among dairy cattle and goats. Therefore, when evaluating the occupational and foodborne risks, MRSA carriage and infection should be taken into account.
Keywords: Methicillin-Resistant Staphylococcus aureus; mléko; farmy; Methicillin; Anti-Bacterial Agents; Farms; leukocidiny; ovce; techniky typizace bakterií; Česká republika; MLST; Dairying; Staphylococcal Infections; stafylokokové infekce; skot; exotoxiny; Czech Republic; Bacterial Typing Techniques; Bacterial Proteins; Bacterial Toxins; ST398; Multilocus Sequence Typing; Methicillin Resistance; bakteriální toxiny; ženské pohlaví; zvířata; MRSA; mlékárenství; type; chromosomal cassette; antibakteriální látky; Cattle; methicilin rezistentní Staphylococcus aureus; Leukocidins; Milk; Goats; Sheep; dairy farm; multilokusová sekvenční typizace; Female; bakteriální proteiny; rezistence na methicilin; Exotoxins; methicilin; kozy; Animals